Report on cardiovascular health and diseases in China 2021: an updated summary - HU, Sheng-Shou (Journal of geriatric cardiology : JGC, 2023)
In 2019, cardiovascular disease (CVD) accounted for 46.74% and 44.26% of all deaths in rural and urban areas, respectively. Two out of every five deaths were attributed to CVD. It is estimated that approximately 330 million individuals in China are affected by CVD. Among them, there are 13 million cases of stroke, 11.4 million cases of coronary heart disease, 5 million cases of pulmonary heart disease, 8.9 million cases of heart failure, 4.9 million cases of atrial fibrillation, 2.5 million cases of rheumatic heart disease, 2 million cases of congenital heart disease, 45.3 million cases of lower extremity artery disease, and 245 million cases of hypertension. With the dual challenges of population aging and a steady increase in the prevalence of metabolic risk factors, the burden of CVD in China is expected to continue rising. Consequently, new demands arise for CVD prevention, treatment, and the allocation of medical resources. Emphasizing primary prevention to reduce disease prevalence, increasing the allocation of medical resources for CVD emergency and critical care, and providing rehabilitation services and secondary prevention to reduce the risk of recurrence, rehospitalization, and disability among CVD survivors are of paramount importance. Hypertension, dyslipidemia, and diabetes affect millions of individuals in China. Since blood pressure, blood lipids, and blood sugar levels often rise insidiously, vascular disease and serious events such as myocardial infarction and stroke occur by the time they are detected in this population. Therefore, it is crucial to implement strategies and measures to prevent risk factors such as hypertension, dyslipidemia, diabetes, obesity, and smoking. Furthermore, greater efforts should be directed towards assessing cardiovascular health status and conducting research on early pathological changes to enhance prevention, treatment, and understanding of CVD.